1995
DOI: 10.1111/j.1469-7610.1995.tb01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Enuresis in ADHD and Non‐ADHD Children

Abstract: Enuresis and attention deficit hyperactivity disorder (ADHD) are common childhood disorders that often co-occur. Although each has been linked to neurodevelopmental immaturity and increased risk for psychopathology, the clinical correlates of enuresis remain unclear. Subjects were 140 6-17-year-old boys with DSM-III-R ADHD and 120 non-ADHD controls. Information on enuresis and psychiatric diagnoses was obtained in a standardized manner blind to the child's clinical status. Our results show that (1) enuresis di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
2
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 36 publications
2
37
2
4
Order By: Relevance
“…In (ADHD) co-morbidity studies, with a crosssectional design (Tables 2 and 3), the same shortcomings are observed, seen in the strong diversity in the definition of enuresis that results in a co-occurrence range between 28.6% and 40% [3,4,5,25]. The lack of standardization hampers the comparison and interpretation of research findings.…”
Section: Diagnosis Of Enuresismentioning
confidence: 55%
See 1 more Smart Citation
“…In (ADHD) co-morbidity studies, with a crosssectional design (Tables 2 and 3), the same shortcomings are observed, seen in the strong diversity in the definition of enuresis that results in a co-occurrence range between 28.6% and 40% [3,4,5,25]. The lack of standardization hampers the comparison and interpretation of research findings.…”
Section: Diagnosis Of Enuresismentioning
confidence: 55%
“…In spite of this, the co-occurrence of ADHD and enuresis is consistently reported in approximately 30% of patients [4,5]. Robson et al [27] worked out that a 6-year-old child with ADHD has 2.7-times more chance of suffering co-morbid nocturnal enuresis than its peers and 4.5-times more chance of suffering diurnal enuresis.…”
Section: Diagnosis Of Adhd and Other Externalizing Problemsmentioning
confidence: 95%
“…In einer anderen Studie von 140 Kindern mit ADHD hatten 25% eine Enuresis nocturna. Bei den 120 Kontrollen waren es nur 10,8% [6]. Mögliche gemeinsame neurobiologische Zusammenhänge sind nicht geklärt, jedoch werden die beiden Störun- …”
Section: Komorbidität Von Spezifischen Psychischen Auffälligkeiten Beunclassified
“…Approximately 20-30% of children with enuresis show also ADHD [13]. The opposite, that is, presence of ADHD in a population of individuals with enuresis, has several diverse results in literature: from about 10% [14,15] to 30% [13]. Baeyens et al [16] distinguish that prevalence in accordance with the subtypes of ADHD, finding out 15% of the combined ADHD and 22.5% of the ADHD with predominant attention-deficit, which would justify the divergence between studies.…”
mentioning
confidence: 93%
“…The association between bedwetting and ADHD is frequently reported in both directions. Approximately 20-30% of children with enuresis show also ADHD [13]. The opposite, that is, presence of ADHD in a population of individuals with enuresis, has several diverse results in literature: from about 10% [14,15] to 30% [13].…”
mentioning
confidence: 99%